The Importance of Character Development in the Digital Age in the 21st Century: Pentingnya Pengembangan Karakter di Era Digital pada Abad 21 - Ilham Samudra Sanur; Ridha, M Rasyid; Muh. Firmansyah; Randiawan (Jurnal Riseta Soshum, 2025)
The development of information and communication technology has significantly reconstructed social, cultural, and educational structures, thereby requiring the strengthening of ethical values and integrity from an early age. This study aims to explore the urgency of character development in the digital age and the role of character education in shaping a generation that is not only technologically competent but also has integrity. The method used is a qualitative approach through literature review by examining various relevant sources and documents. The results of the study indicate that the integration of Pancasila values and local wisdom in character education is crucial for fostering morality, integrity, and critical thinking skills amid the prevalence of hoaxes and cyberbullying. The roles of parents and educators are critical in guiding the healthy use of technology. Furthermore, strengthening soft skills such as communication, collaboration, and adaptability is necessary to navigate the dynamics of the digital world. In conclusion, collaboration between schools, families, and communities in integrating character education, digital literacy, and soft skills development in a holistic manner is key to producing a generation that is morally resilient and digitally competent.